Mechanics, energetics and implementation of grounded running technique: a narrative review. Issue 1 (4th December 2020) - Davis, Sheeba; Fox, Aaron; Bonacci, Jason; Davis, Fiddy
Abstract : Grounded running predominantly differs from traditional aerial running by having alternating single and double stance with no flight phase. Approximately, 16% of runners in an open marathon and 33% of recreational runners in a 5 km running event adopted a grounded running technique. Grounded running typically occurs at a speed range of 2–3 m·s −1, is characterised by a larger duty factor, reduced vertical leg stiffness, lower vertical oscillation of the centre of mass (COM) and greater impact attenuation than aerial running. Grounded running typically induces an acute increase in metabolic cost, likely due to the larger duty factor. The increased duty factor may translate to a more stable locomotion. The reduced vertical oscillation of COM, attenuated impact shock, and potential for improved postural stability may make grounded running a preferred form of physical exercise in people new to running or with low loading capacities (eg, novice overweight/obese, elderly runners, rehabilitating athletes). Grounded running as a less impactful, but metabolically more challenging form, could benefit these runners to optimise their cardio-metabolic health, while at the same time minimise running-related injury risk. This review discusses the mechanical demands and energetics of grounded running along with recommendations and suggestions to implement this technique in practice.